Factors stimulating content marketing - Naser Azad; Seyed Mohsen Seyed AliAkbar; Sima Zomorodian (Management Science Letters)
This paper presents an empirical investigation to determine factors influencing on content marketing in banking industry. The study designs a questionnaire consists of 40 questions in Likert scale and distributes it among 550 randomly selected regular customers of Bank Mellat in city of Tehran, Iran and 400 properly filled questionnaires are collected. Cronbach alphas for all components of the survey are well above desirable level. Using principle component analysis with Varimax rotation, the study has determined six factors influencing the most on content marketing including organization, details, having new ideas, quality, sensitivity and power while the last component contains only two subcomponents and is removed from the study.